2023
DOI: 10.1093/aob/mcad138
|View full text |Cite
|
Sign up to set email alerts
|

Living at the edge: the functional niche occupation of woody plant communities in the submediterranean ecotone

Enrique G de la Riva,
Iván Prieto,
Sergio de Tomás Marín
et al.

Abstract: Background and aims Submediterranean areas are rich ecotones, where slight modifications in environmental conditions can lead to substantial changes in the composition of plant communities. They thus offer an ideal scenario to examine plant community assembly. In this study, we followed a trait-based approach including intraspecific variability to elucidate (1) the relationship between niche occupancy components and species richness, (2) the processes governing the assembly of these communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…At the other end of the environmental gradient (see also de la Riva et al, 2023), we found the F. sylvatica community with predominantly acquisitive strategies at the whole plant level. In fact, species with a profligate water-use strategy, such as F. sylvatica (de Tomaś , dominated the lowest areas of Montejo where deeper soils are found (de la Riva et al, 2023), which could explain the shift in the hydraulic dimension along the soil depth gradient better than soil nutrients. This profligate use of water and nutrients of F. sylvatica makes it a strong fast-growing species that promotes strong competitive exclusion (Meyer et al, 2003;Rodrıǵuez-Calcerrada et al, 2011;Castaño-Santamaria et al, 2021).…”
Section: Trait Distribution and Environmental Effects On Community As...mentioning
confidence: 59%
See 4 more Smart Citations
“…At the other end of the environmental gradient (see also de la Riva et al, 2023), we found the F. sylvatica community with predominantly acquisitive strategies at the whole plant level. In fact, species with a profligate water-use strategy, such as F. sylvatica (de Tomaś , dominated the lowest areas of Montejo where deeper soils are found (de la Riva et al, 2023), which could explain the shift in the hydraulic dimension along the soil depth gradient better than soil nutrients. This profligate use of water and nutrients of F. sylvatica makes it a strong fast-growing species that promotes strong competitive exclusion (Meyer et al, 2003;Rodrıǵuez-Calcerrada et al, 2011;Castaño-Santamaria et al, 2021).…”
Section: Trait Distribution and Environmental Effects On Community As...mentioning
confidence: 59%
“…In each FI, 125 circular plots of 30-m diameter were systematically established in a 100 x 100 m square grid covering the entire forest. Based on the last FI, we divided the forest into six different areas (communities hereafter) according to the distribution of the three most abundant tree species, i.e., beech, Pyrenean oak and sessile oak (see also de la Riva et al, 2023). An additional community dominated by shrubs where trees are scarce and dispersed was included.…”
Section: Sampling Designmentioning
confidence: 99%
See 3 more Smart Citations